2017
DOI: 10.3390/w9120934
|View full text |Cite
|
Sign up to set email alerts
|

Water Security in Times of Climate Change and Intractability: Reconciling Conflict by Transforming Security Concerns into Equity Concerns

Abstract: This paper considers how to achieve equitable water governance and the flow-on effects it has in terms of supporting sustainable development, drawing on case studies from the international climate change adaptation and governance project (CADWAGO). Water governance, like many other global issues, is becoming increasingly intractable (wicked) with climate change and is, by the international community, being linked to instances of threats to human security, the war in the Sudanese Darfur and more recently the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Furthermore, the threats can be accentuated by limited economic participation and weak and dysfunctional institutions as instantiated by weak democracies and institutions (Homer-Dixon, 1994;Klare, 2001, pp. 138-147;Powell et al, 2017) as found in countries of the Nile basin. The present global water and sanitation crisis is attributable to a combination of interlinked factors-poverty, inequality, and unequal power relationships (Homer-Dixon, 1994;UN-Water, 2013;Zeitoun, 2011) as well as climate change, social and legislative constructions, rapid population growth, and further technological/economic developments that result from migration patterns threatening the overall security situation (Klare, 2001, pp.…”
Section: Theoretical Frameworkmentioning
confidence: 88%
See 1 more Smart Citation
“…Furthermore, the threats can be accentuated by limited economic participation and weak and dysfunctional institutions as instantiated by weak democracies and institutions (Homer-Dixon, 1994;Klare, 2001, pp. 138-147;Powell et al, 2017) as found in countries of the Nile basin. The present global water and sanitation crisis is attributable to a combination of interlinked factors-poverty, inequality, and unequal power relationships (Homer-Dixon, 1994;UN-Water, 2013;Zeitoun, 2011) as well as climate change, social and legislative constructions, rapid population growth, and further technological/economic developments that result from migration patterns threatening the overall security situation (Klare, 2001, pp.…”
Section: Theoretical Frameworkmentioning
confidence: 88%
“…It will act as a conflict multiplier by amplifying existing environmental stresses, creating new ones, exacerbating water and food insecurity, and adding to the pressures on weak, corrupt, or repressive governments (which by their nature will find it hard to respond to such situations) but will also threaten more stable and effective ones (Homer-Dixon, 1994;Ketzek & Mazo, 2014, p. 143). Powell et al (2017) state that "Enabling water security requires more than being attentive to conflicts of interests between stakeholders, it requires recognizing that different position-holders make competing claims, not over divergences in interests but rather over who should have agency in the enactment of governance." We posit that conflicts of interest and conflicts of position frame water governance among riparian states in the Nile Basin.…”
Section: Reconciling Climate Change and Water Governancementioning
confidence: 99%
“…The most long-standing water governance framework is the Integrated Water Resource Management (IWRM) that promotes coordinated management actions in relation to environmental sustainability, economic efficiency, and social equity [24]. Beyond the principles of integration across actions and their consequences, consideration of the "triple bottom line", an exhortation to ensure participatory approaches and the full inclusion of women in management, IWRM is non-prescriptive.…”
Section: Existing Water Governance Principles and Frameworkmentioning
confidence: 99%
“…This wicked situation grows out of complex and dynamic systems that are characterized by non-equilibrium properties, as exemplified by droughts and floods. Similarly, the systemic nature of nutrient enrichment leads to "complex interdependencies between the biophysical and socio-economic domains" and the amplification and export of problems between: upstream and downstream, terrestrial and marine contexts, societal intersections, and nation states (Powell et al 2017). Moreover, other existing pressures such as climate change are projected to amplify enrichment (Bartosova et al 2019) and the flow-on effects that magnify other issues such as food security, renewable energy and biodiversity.…”
Section: Introductionmentioning
confidence: 99%